Synthesis and evaluation of pH dependent hydrogels for controlled release of Venlafaxine HCl - Nasir Abbas; Qazi Amir Ijaz; Amjad Hussain; Nadeem Irfan Bukhari (British Journal of Pharmacy, 2018)
pH dependent hydrogel formulations of venlafexine HCl were prepared by free radical polymerization method using polyethylene glycol as polymer. Various samples were prepared with varying concentration of polymer, monomer and cross-linker to study their effect on gel swelling, diffusion characteristics and drug release. Swelling was found to be increased with increase in pH. Increase in acrylic acid concentration increases swelling while increase in cross-linker concentration has an opposite effect on swelling. Drug release study was performed in pH 1.2, 5.5 and 7.5 for 12 hours at 37 oC and drug release was found to increase in higher pH. Prepared hydrogel preparations were also characterized by PXRD, TGA, SEM and FTIR.